Financial inclusion in rural South Africa: A qualitative approach - Munacinga Simatele; Loyiso Maciko (Journal of Risk and Financial Management, 2022)
Financial inclusion efforts have resulted in a rapid increase in access to financial services. However, the usage of these financial services has not expanded at the same pace, especially in rural areas. The paper explores the factors that have caused usage to lag behind access using a qualitative approach. Data is collected from two predominantly rural provinces in South Africa using focus group discussions. While supply-side factors of distance and transaction costs are important, demand-side factors, including lack of employment, low and irregular incomes, financial illiteracy, and risk and trust perceptions, play a more significant role. We suggest that creating an enabling environment for the development of mobile money could overcome proximity barriers and result in better inclusion of rural communities. There is a need to invest in technology to improve network and Internet reception in rural areas. In addition, the government needs to reconsider the exclusive issuance of e-money by banks. Partnerships with supermarket money markets also have the potential to expand financial inclusion. Moreover, post-adoption financial education should complement efforts to expand financial inclusion. Simplified and transparent cost structures could help resolve the mistrust of banks.
Keywords: 650; financial literacy; financial inclusion; access; usage